Identification and characterization of novel MPC1 gene variants causing mitochondrial pyruvate carrier deficiency. Issue 2 (8th January 2022) - Jiang, Huafang; Alahmad, Ahmad; Fu, Song; Fu, Xiaoling; Liu, Zhimei; Han, Xiaodi; Li, Lanlan; Song, Tianyu; Xu, Manting; Liu, Shanshan; Wang, Junling; Albash, Buthaina; et al.
Abstract: Pyruvate, the end product of glycolysis, is a key metabolic molecule enabling mitochondrial adenosine triphosphate synthesis and takes part in multiple biosynthetic pathways within mitochondria. The mitochondrial pyruvate carrier (MPC) plays a vital role in transporting pyruvate from the cytosol into the organelle. In humans, MPC is a hetero‐oligomeric complex formed by the MPC1 and MPC2 paralogs that are both necessary to stabilize each other and form a functional MPC. MPC deficiency (OMIM#614741) due to pathogenic MPC1 variants is a rare autosomal recessive disease involving developmental delay, microcephaly, growth failure, and increased serum lactate and pyruvate. To date, two MPC1 variants in four cases have been reported, though only one with a detailed clinical description. Herein, we report three novel pathogenic MPC1 variants in six patients from three unrelated families, identified within European, Kuwaiti, and Chinese mitochondrial disease patient cohorts, one of whom presented as a Leigh‐like syndrome. Functional analysis in primary fibroblasts from the patients revealed decreased expression of MPC1 and MPC2. We rescued pyruvate‐driven oxygen consumption rate in patient's fibroblasts by reconstituting with wild‐type MPC1 . Complementing homozygous MPC1 mutant cDNA with CRISPR‐deleted MPC1 C2C12 cells verified the mechanism of variants: unstable MPC complex or ablated pyruvate uptake activity. Furthermore, we showed that glutamine and beta‐hydroxybutyrate were alternative substrates to maintain mitochondrial respiration when cells lack pyruvate. In conclusion, we expand the clinical phenotypes and genotypes associated with MPC deficiency, with our studies revealing glutamine as a potential therapy for MPC deficiency.